2002
DOI: 10.1039/b206258e
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of methanol, acetone and formaldehyde with ice surfaces between 198 and 223 K

Abstract: The rate and extent of physical adsorption of methanol, acetone and formaldehyde on ice were measured as a function of concentration and temperature. The gas-ice interaction was analysed by applying adsorption isotherms to determine temperature dependent Langmuir constants, K(T) and saturation surface coverage, N max . At low coverage a partitioning constant K # (T) was derived. The dependence of K # on temperature is given by K # (T) ¼ 6.24 Â 10 À12 exp(6178/T) cm for methanol and K # (T) ¼ 1.25 Â 10 À10 exp(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
175
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(205 citation statements)
references
References 24 publications
29
175
0
1
Order By: Relevance
“…Further, as a potential Hacceptor, acetone is miscible in any ratio with water as well as other hydrogen bonding liquids, such as small alcohols. Because of its importance the properties of acetone have been investigated in detail in different systems by a variety of experimental methods [1][2][3][4][5][6][7][8][9][10][11][12], and these investigations were well complemented by numerous computer simulation studies of neat bulk liquid acetone [13][14][15][16][17], mixtures of acetone in various proportions with water [18][19][20][21][22][23][24][25][26][27], with other solvents [28][29][30][31][32][33] and solvent mixtures [34], adsorption layer of acetone at the surface of ice [35,36], and aqueous acetone nanoclusters [37].…”
Section: Introductionmentioning
confidence: 99%
“…Further, as a potential Hacceptor, acetone is miscible in any ratio with water as well as other hydrogen bonding liquids, such as small alcohols. Because of its importance the properties of acetone have been investigated in detail in different systems by a variety of experimental methods [1][2][3][4][5][6][7][8][9][10][11][12], and these investigations were well complemented by numerous computer simulation studies of neat bulk liquid acetone [13][14][15][16][17], mixtures of acetone in various proportions with water [18][19][20][21][22][23][24][25][26][27], with other solvents [28][29][30][31][32][33] and solvent mixtures [34], adsorption layer of acetone at the surface of ice [35,36], and aqueous acetone nanoclusters [37].…”
Section: Introductionmentioning
confidence: 99%
“…After obtaining the values of K H , the surface coverage of n-hexane and acetone can be estimated at the lowest temperature investigated. Winkler et al (2002) reported an adsorption capacity of 4.5×10 −6 mol m −2 for acetone on ice. For nhexane θ ≈ 5 % at 1.5 Pa at 211 K and for acetone θ = 13 % at 0.4 Pa and 224 K are obtained for the largest concentrations observed at peak maximum.…”
Section: Adsorption Of Acetone and N-hexanementioning
confidence: 99%
“…For H 2 O 2 , we also used preliminary results of the Max Planck Insitute fur Chemie in Mainz which will be reported in detail elsewhere (Pouvesle et al, manuscript in preparation, 2010). Briefly, partition coefficients for H 2 O 2 were obtained in the MPI laboratory at temperatures between 203 and 233 K in the same apparatus used to study the interaction of several oxidized organic trace gases with ice surfaces at upper tropospheric temperatures (Winkler et al, 2002;von Hessberg et al, 2008). Results were obtained using both single species adsorption of H 2 O 2 and a competitive approach, whereby the displacement of HC(O)OH from the ice surface by adsorbed at 228 K (K linC ≈ 360 cm) is thus more than 2 orders of magnitude larger than the value of 1.6 cm, reported by Clegg and Abbatt (2001) for the temperature range 228-240 K. Figure 6 shows the partition coefficient K linC for the 11 trace gases as a function of the temperature.…”
Section: The Langmuir Theorymentioning
confidence: 99%
“…This equilibrium can be derived from the surface partition coefficient K linC and the maximum number of sites available for adsorption N MAX . A large number of laboratory studies (Abbatt, 1997;Chu et al, 2000;Bartels et al, 2002;Dominé and Rey-Hanot, 2002;Hudson et al, 2002;Hynes et al, 2002;Sokolov and Abbatt, 2002;Winkler et al, 2002;Bartels-Rausch et al, 2004;Peybernès et al, 2004;Cox et al, 2005;Ullerstam and Abbatt;2005;Kerbrat et al, 2007;von Hessberg et al, 2008) have been recently assessed by the IUPAC Subcommittee on Gas Kinetic Data Evaluation (see Crowley et al, 2010 and http://www.iupac-kinetic.ch.cam.ac.uk) to derive the partition coefficients for several species of atmospheric interest. In these simulations made for low temperature (<250 K), the thermodynamic state of the ice surface (solid, quasi-liquid or disordered surface layers) is not considered.…”
Section: Introductionmentioning
confidence: 99%